Endoscopic management of complications of acute pancreatitis: an update on the field. (2nd December 2018) - Aghdassi, Ali; Simon, Peter; Pickartz, Tilman; Budde, Christoph; Skube, Mariya E.; Lerch, Markus. M.
ABSTRACT: Introduction : Acute pancreatitis is a frequent, nonmalignant gastrointestinal disorder leading to hospital admission. For its severe form and subsequent complications, minimally invasive and endoscopic procedures are being used increasingly, and are subject to rapid technical advances. Areas covered : Based on a systematic literature search in PubMed, medline, and Web-of-Science, we discuss the currently available treatment strategies for endoscopic therapy of pancreatic pseudocysts, walled-off pancreatic necrosis (WON), and disconnected pancreatic duct syndrome (DPDS), and compare the efficacy and safety of plastic and metal stents. A special focus is placed on studies directly comparing different stent types, including lumen-apposing metal stents (LAMS) and clinical outcomes when draining pseudocysts or WONs. The clinical significance and endoscopic treatment options for DPDS are also discussed. Expert commentary : Endoscopic therapy has become the treatment of choice for different types of pancreatic and peripancreatic collections, the majority of which, however, require no intervention. The use of LAMS has facilitated drainage and necrosectomy in patients with WON or pseudocysts. Serious complications remain a problem in spite of high technical and clinical success rates. DPDS is an increasingly recognized problem in the presence of pseudocysts or WONs but evidence for endoscopic stent placement in this situation remains insufficient.